PENGARUH INTERAKSI MEDIA DAN GAYA KOGNITIF TERHADAP PENGUASAAN KONSEP BANGUN DATAR DAN BANGUN RUANG - Effendi, Aguseri -; -, Sjarkawi -; -, Asrial - (Program Magister Teknologi Pendidikan Universitas Jambi, 2011)
This study is aimed to know the influence of media interaction and cognitive style toward concept mastery of Mathematics. The independent variable is the usage of media, the moderator variable is cognitive style as measured by the Childrenâ€™s Embedded Figures Test (CEFT), and the dependent variable is the mastery of concepts.By using quasi-experimental design, sample of the research is divided into two groups as experiment and control group.Â The experiment and control groups are students of grade 5-th SDN 16 / X Nipah Panjang who taught with different methods. The experiment group is taught by teacher using interactive media and the control group is not. By using Two-way ANOVA analysis and Tukey analysis it can be shown that interactive-media usage and cognitive style give significant effect on studentsâ€™ mastery in Mathematics concept. Keywords: interactive CD media, PowerPoint media, cognitive styles